WANE CUTTING INFLUENCE ON LUMBER VOLUME - Kulikova, Nadezhda (Innovation in Woodworking Industry and Engineering design, 2016)
When cutting lumber in the sawmill, if there is more left wane, the more voluminous output blanks. Efforts in the sawmill increase, but the increase in volume output blanks pays for effort and makes a profit.This increase in the volumetric output of lumber due to the cutting board in width in two stages – in the sawmill and woodworking shop after drying lumber. At the same time, the costs related to that part of the drying lumber, which will be removed in a woodworking shop, will be repaid by increasing the volumetric output of billets produced lumber.Thus, the timber with a predetermined quantity wane after leaving the drying room may be used in such a form as pieces for a wooden house.